O efeito do inibidor de Fosfatidilinositol 3-Quinase Delta (PI3K δ) na mucosite intestinal induzida por irinotecano em camundongos - Lopes, Marina Helena da Silva (2023)
Colorectal Cancer is one of the most common cancers, treated with chemotherapy regimens based on the chemotherapy Irinotecan, a potent inhibitor of Topoisomerase I, which, when treating the disease, causes side effects, including intestinal mucositis. Mucositis is an inflammatory effect resulting from the toxicity of the accumulation of irinotecan metabolites, mainly SN-38, which induces cell death, activates inflammasomes, interacts with Toll-Like 4 receptors, and promotes the activation of NF-κB with increased pro-inflammatory cytokines. PI3K enzymes may be important intermediates in signaling and regulation of TLRs. Thus, the aim of this work was to evaluate the role of PI3K in its δ isoform in irinotecan-induced intestinal mucositis. Male C57BL/6 mice (n=6-8) weighing between 20-24g were used (CEUA approved No. 5132240718). In the mice, irinotecan 75mg/kg i.p. (intraperitoneal route) and/or PI3Kδ inhibitor 3mg/kg orally were administered for 4 days. The weight of the mice was measured daily. On the 7th day, the animals were euthanized and samples were collected for total leukocyte count, myeloperoxidase dosage, intestinal length measurement, intestinal morphometry, oxidative stress, IL-1β dosage, and immunofluorescence intensity analysis for F4/80, FOXP-3, and p-AKT. Statistical analysis was performed by GraphPad Prism version 8.0 considering p<0.05 as statistical significance. The results revealed an intense inflammatory process during PI3Kδ enzyme inhibition, as animals treated with the inhibitor associated with Irinotecan had higher neutrophil infiltration (3428 neutrophils/mg tissue), increased expression of macrophages in the intestinal tissue (3, 8%), decreased expression of reg T cells (14.13%), greater weight loss (84.7%), decreased small intestinal length (34.07 cm), decreased villus area (31.12), and changes in intestinal and liver architecture when compared to the irinotecan group (1905 neutrophils; 2.1%; 22%; 89.4%; 37.21 cm; 39.10 respectively). Furthermore, the Irinotecan + Inhibitor group evidenced increased phospho-AKT expression when compared to the negative control group. Therefore, it is concluded that the association of PI3Kδ inhibitors and irinotecan exacerbate the inflammatory process and may lead to greater toxicity.